"Early" Reoperation to Treat Complications Following Laparoscopic Colorectal Surgery: The Sooner the Better. Issue 6 (18th December 2021) - Rotholtz, Nicolas A.; Angeramo, Cristian A.; Laporte, Mariano; Matzner Perfumo, Mariana; Schlottmann, Francisco; Bun, Maximiliano E.
Abstract : Background: Some postoperative complications after laparoscopic colorectal surgery (LCS) require reoperation to be treated. However, if the timing to perform this reoperation has some influence on outcome remains elusive. The aim of this study was to analyze if the timing to perform the reoperation has some influence in postoperative outcomes. Methods: A retrospective analysis of patients undergoing LCS and required a reoperation during the period 2000 to 2019 were included. The cohort was divided into 2 groups: early reoperation (ER): ≤48 hours or delayed reoperation (DR): ≥48 hours based on the interval between the suspicion of a complication and reoperation. Demographics, operative variables, and postoperative outcomes were compared between groups. Results: A total of 1843 LCS were performed, 68 (43%) were included in ER and 91 (57%) in DR. A computed tomography scan was less frequently performed in the ER (ER: 45% vs. DR: 70%; P =0.001). The rates of re-laparoscopy (ER: 86% vs. 73%; P =0.04) and negative findings in the reoperation (ER: 13% vs. DR: 1%, P =0.001) were higher in ER. There were no statistically significant differences in overall major morbidity (ER: 9% vs. DR: 21%; P =0.06) and mortality rate (ER: 4% vs. DR: 8.7%; P =0.28) between groups. The need of intensive care unit was significantly higher and the length of stay longer for patients in the DR group. Conclusions: Despite a greater risk of negative findings, ER within 48 hours after the suspicion of a complication after a LCS offers higher chances of using a laparoscopic approach and it could probably provide better postoperative outcomes.